Child Expenditure: The Role of Working Mothers, Lone Parents, Sibling Composition and Household Provision - Lisa Farrell; Michael A. Shields (Institute for the Study of Labor (IZA), 2001)
This paper uses detailed diary information from the British Family Expenditure Survey (FES) to investigate the expenditure patterns of school-age children. We estimate a Quadratic Almost Ideal Demand System, and find that, whilst most commodities are normal goods, sweets and toys are luxury items for children. Children of lone parents have lower budget shares for expenditure on soft drinks, leisure, personal goods and books/magazines, but higher budget shares for expenditure on sweets and vice products (alcohol, cigarettes and gambling). Having a working mother increases child expenditure on food products and toys. A higher parental budget share, on any given commodity, is generally associated with an increased child budget share suggesting that children mimic their parent?s expenditure patterns.
Keywords: D12; J13; D11; 330; Child expenditure; quadratic almost ideal demand system; lone parents; working mothers; sibling composition; Kinder; Konsumentenverhalten; Verbraucherausgaben; Alleinerziehende; Nachfragesystem; Schätzung; Großbritannien